OSKAR GOTTLIEB BLARR I JEGO KULTUROWY WKŁAD W POJEDNANIE POLSKO-NIEMIECKIE - Gładkowski, Krzysztof (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The author presents the figure of Oskar Gottlieb Blarr, a composer, organist, cantor and conductor from Düsseldorf, who received a honorary doctorate from the University of Warmia and Mazury in Olsztyn on October 14, 2016. Oskar Gottlieb Blarr was born in 1934 in Sandlack/Bartenstein (today Sędławki near Bartoszyce). He is still connected to his homeland where his musical talent and passion, especialy for organs, were born. Oskar Gottlieb Blarr is convinced that the improvement of the relations between the Polish and Germans was possible mainly through art. Blarr assigns a special rlole to music as a mean of international understanding in its own right, thw role which, accroding to him, is not sufficiently appreciated. The important figures who led Oscar Gottlieb Blarr to know Polish culture were prominent avant-garde composers, such as Krzysztof Penderecki, Witold Lutosławski, Kazimierz Serocki, Krzysztof Meyer, Włodzimierz Kotański, and conductors Witold Rowicki, Jan Krenz, Henryk Czyż. Their achievements have gained recognition in Germany and constituted a tool for Polish-German reconciliation. Oskar Gottlieb Blarr studied composition with Krzysztof Penderecki in Essen and Berlin. Contact with Penderecki resulted in aused the Blarr’s renewed interest his former homeland – East Prussia. He arrived to Poland in 1970 and performed as an organist with the Symphony Orchestra of Cologne, which was conducted by Witold Rowicki, at Warsaw Autmun Festival. Then he went to Bartoszyce, to the church of St. John the Evangelist and Our Lady of Czestochowa in search of the remains of Baroque organs. From that time until today Blarr has done everything in his power to restate the former glory and sound to historic organs in various places Poland, especially Warmia and Mazury. Moreover, Blarr gave many concerts in Poland and organized performances of Polsih musicians in Germany. The concerts of Polish and German artists may serve as an example of Blarr’s activity for the Polish-German concilation. Blarr prepared and conducted following concerts: the oratory Quo vadis Opus 30 by FelixNowowiejski in Düsseldorf in 1989, his own Symphony No. 1 Janusz Korczak en karem concerto in Warsaw in 2003, and another of his own symphonies – Symphony No. 3 in honor of Immanuel Kant Zum ewigen Frieden in Olsztyn in 2005. Blarr dedicated many of his compositions to outsanding Poles including: cantata In te Domine speravi (1970) dedicated to priest, martyr and saint Maximilian Kolbe, Symphony No. 1 Janusz Korczak en karem concerto, dedicated to Janusz Korczak (1985, 1992 premiere at the Tonhalle in Düsseldorf) and the composition for flute, guitar and bass Das Heimweh des Walerian Wróbel/The homesickness of Walerian Wróbel (premiere in Düsseldorf in 2005). These works were carried out under his leadership in Poland and Germany. Among these works, his Symphony No. 4 In honor of Nicolaus Copernicus has special importance in Blarr’s work for Polish-German reconciliation. Its premiere was in October 2011 at the Tonhalle in Düsseldorf.